Sharia Entrepreneurial Ethics in Social Commerce: A Critical Analysis of Predatory Pricing on UMKM Sustainability - Ahmad Rokhim; Rizqi Egy Gumilang; Muhammad Aminul Wahid (Journal of Creative Power and Ambition (JCPA), 2026)
The development of social commerce has transformed the structure of digital trade in Indonesia by integrating social interaction, content promotion, and commercial transactions within a single ecosystem. While this transformation creates substantial opportunities for UMKMs to expand their market reach, it simultaneously poses serious challenges, including predatory pricing, platform dominance, and market access disparities that disadvantage small business actors. This article aims to analyze predatory pricing practices in social commerce through the lens of Sharia entrepreneurial ethics and assess their implications for the sustainability of local UMKMs. Applying a qualitative-normative approach, this study employs a critical literature review of Islamic economic literature, official regulations, and relevant national and international journals. The findings indicate that predatory pricing in social commerce is not merely a low-pricing strategy, but a market elimination instrument that erodes turnover, diminishes competitiveness, and fosters UMKM dependency on major digital platforms. From a Sharia perspective, such practices contradict the principles of justice, the prohibition of harm (la darar wa la dirar), transparency, and public interest (maslahah). This article emphasizes that strengthening regulations, algorithmic transparency, UMKM protection, and the development of Islamic business ethics in the digital sphere are urgent necessities to preserve local economic sustainability.